Selected essays on the history of Scots law. Volume 1, Law, lawyers, and humanism - Cairns, John W. (Edinburgh : Edinburgh University Press, 2018)
These volumes collect together and reprint a selection of some of the many articles and essays published by Professor John W. Cairns over a distinguished career in legal history.
Previously issued in print: 2015.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 19, 2017).
Keywords: Law -- Scotland -- History; Lawyers -- Scotland -- History; Humanism -- Scotland; Law; Laws of specific jurisdictions & specific areas of law